Laparoscopic splenectomy after trauma: Who, when and how. A systematic review - Fransvea, Pietro (J Minim Access Surg, 2021)
IMPORTANCE: A deep knowledge of the indication for laparoscopic splenectomy (LS) in trauma case can lead trauma surgeon to offer in a wider number of situations a minimally invasive approach to a common injuries. OBJECTIVE: To present and review the advantages and disadvantages of laparoscopic approach for spleen trauma and to identify patient whose can benefit from a minimally invasive approach versus patient that need open surgery to assess the whole severity of trauma. EVIDENCE REVIEW: A systematic review was performed according to the PRISMA statement in order to identify articles reporting LS after trauma. A literature search was performed through MEDLINE (through PubMed), Embase and Google Scholar from January 1990 to December 2018. Studies conducted on animals were not considered. All other laparoscopic procedures for spleen trauma were excluded. RESULTS: Nineteen articles were included in this study, reporting 212 LS after trauma. The most study includes blunt trauma patient. All LS were performed in haemodynamically stable patient. Post-operative complications were reported in all articles with a median post-operative morbidity rate of 30 patients (14.01%), including 16 (7.5%) post-operative deaths. CONCLUSIONS AND RELEVANCE: This article reports the feasibility and safety of a minimally invasive approach for common trauma injuries which can help non-advanced laparoscopic skill trauma surgeon to develop the best indication to when to adopt this kind of approach.